Topological Dirac states in transition-metal monolayers on graphyne. Issue 18 (17th April 2019) - Wang, Kai; Zhang, Yun; Zhao, Wei; Li, Ping; Ding, Jian-Wen; Xie, Guo-Feng; Guo, Zhi-Xin
Abstract : The electronic properties of Hf–graphyne show that there are three Dirac cones appearing around the K point near the E F . Abstract : Realizing topological Dirac states in two-dimensional (2D) magnetic materials is particularly important to spintronics. Here, we propose that such states can be obtained in a transition-metal (Hf) monolayer grown on a 2D substrate with hexagonal hollow geometry (graphyne). We find that the significant orbital hybridizations between Hf and C atoms can induce sizable magnetism and bring three Dirac cones at/around each high-symmetry K ( K ′) point in the Brillouin zone. One Dirac cone is formed by pure spin-up electrons from the d z 2 orbital of Hf, and the remaining two are formed by crossover between spin-up electrons from the d z 2 orbital and spin-down electrons from the hybridization of the d xy / x 2 − y 2 orbitals of Hf atoms and the p z orbital of C atoms. We also find that the spin–orbit coupling effect can open sizable band gaps for the Dirac cones. The Berry curvature calculations further show the nontrivial topological nature of the system with a negative Chern number C = −3, which is mainly attributed to the Dirac states. Molecular dynamics simulations confirm the system's thermodynamic stability approaching room temperature. The results provide a new avenue for realizing the high-temperature quantum anomalous Hall effect based on 2D transition-metals.